Profile of children hospitalizations by primary care sensitive conditions - Beatriz Rosana Gonçalves de Oliveira Toso; Cláudia Ross; Caroline Wink Sotti; Scaleti Vanessa Brisch; Jéssica Mayara Cardoso (Universidade Estadual de Maringá, 2016)
Hospitalization for primary care sensitive conditions is a type of hospitalization that may be reduced or avoided if conditions are properly and effectively diagnosed and treated within Primary Health Care. To identify Brazilian rates of morbidity in 0 - 4 year-old children and hospitalization rates for primary care sensitive conditions rates in a pediatric unit of a public hospital in Cascavel, Paraná State, Brazil. Quantitative research whose data were retrieved from the Hospital Information System database - Datasus and from the records of the Medical and Statistical File Service of the hospital, with regard to hospital records of 220 children between January and December 2012, with an instrument specifically developed for research and analysis in descriptive statistics. National hospitalization rates for primary care sensitive conditions were predominant in children under one year and in the northern (657.56) and southern (621.18) regions, underscoring pneumonia. They accounted for 23.30% of hospitalizations, with 15.03% for respiratory diseases in the medical institution under analysis. Respiratory diseases were the main cause of hospitalization for primary care sensitive conditions and in children under one year old. Results suggest an increase in investment for prevention of these diseases in primary health care.